BAHASA, KOMUNIKASI POLITIK DAN IDEOLOGI - Rofiatull Andawiyah (OKARA: Jurnal Bahasa dan Sastra, 2016)
Language is a power, it has a an important role to reach special goal. The use of language in superintensif, including the abuse of language with its various aspects so prominent in the world of poliitk, especially in Indonesia. In the era of globalization of the market and current information, it is difficult to imagine the existence of the forum or the stage of communication of political that is free from the influence of the market or the state. Its a product of fight and political engineering has given rise to a power structure that emphasizes more on the role of the executive that is greater than the legislative or judicial branches. Some distortion of language in political communication is the language as a mask, as a project to forget. The use of language is distorted, among others, that the power of a garden owned by the ruler can still survive. The availability of public space will be effective for the discourse on the counterculture if offset by structural changes in society, especially regarding the relationship between the elite with the masses.